Analisis Sektor Unggulan di Kabupaten Klungkung - Rabbani, Burhanuddin; Yasa, I Nyoman Mahaendra (Jurnal Ilmiah Wahana Pendidikan, 2025)
Economic growth in 9 regencies/cities in Bali Province in 2019 when the economy was still stable, Klungkung Regency had the lowest economic growth of 5.42 percent. In 2023, Klungkung Regency had economic growth of 4.70 percent, ranking fourth out of 9 regencies in Bali Province. This study aims to analyze the leading sectors in Klungkung Regency. This study uses a quantitative research design using quantitative data types and secondary data sources. The data collection method used is non-participant observation and the data analysis techniques used are location quotient, shift share analysis, Dynamic Location Quotient analysis, Klassen typology analysis, and overlay analysis. The results of this study show that there are eight sectors in Klungkung Regency which are base sectors based on the results of the LQ study. Based on the shift share analysis, the Information and Communication sector is the sector that has the largest contribution in Klungkung Regency. The prospective sector in Klungkung Regency is dominated by almost all sectors with 16 sectors based on the results of the DLQ analysis. The sectors included in quadrant I in the economic sector classification based on the Klassen analysis typology are the Agriculture, Forestry, and Fisheries sectors, and the Government Administration, Defense and Mandatory Social Security sectors. The leading sectors in Klungkung Regency based on the overlay analysis include the Agriculture, Forestry, and Fisheries sectors, and the Government Administration, Defense and Mandatory Social Security sectors. The implication of this research is that the leading sectors or sectors that are the basis and become superior in Klungkung Regency do not only focus on the primary sector, but there are already many secondary and tertiary sectors that contribute more to the regional economy.